Pengaruh financial literacy, self control, dan sikap kepribadian terhadap perilaku menabung masyarakat kelas menengah - Sri Rahayu Ningsih (Jurnal Kajian Manajemen dan Wirausaha, 2022)
The purpose of this study is to examine the saving behaviour model, spesifically we test: (1) the effect of financial literacy on saving behaviour; (2) the effect of  self control on saving behaviour; (3) the effect of personality traits on saving behaviour and (4) the effect of self control on saving behaviour through financial literacy as moderating variabel.  The study uses a quantitative approach using primary data obtained through questionnaires distributed online. The sample for this research  was 125 respondents from middle class society. The research data processing technique using  SmartPLS software version 3.3.3. The data were analyzed by using descriptive analysis. The result showed that (1) financial literacy has a positive and significant effect on saving behaviour, (2) self control has a positive and significant effect on saving behaviour, (3) personality traits has a positive and significant effect on saving behaviour and (4) financial literacy doesnt have a significant effect but has a positive effect to moderate the relationship between the self control on saving behaviour